EXPERIMENTAL DETERMINATION OF THE ACTIVITY-COMPOSITION RELATIONS AND PHASE EQUILIBRIA OF H2O-CO2-NACL FLUIDS AT 500°C, 500 BARS - Anovitz L.M.; Labotka T.C.; Blencoe J.G.; Horita J. (My University, 2004)
An understanding of the activity-composition (a-X) relations and phase equilibria of halite-bearing, mixed-species supercritical fluids is critically important in many geological and industrial applications. We have performed experiments on H2O-CO2-NaCl fluids at 500°C, 500 bar, to obtain accurate and precise data on their a-X relations and phase equilibria. Two kinds of experiments were performed. First, H2O-CO2-NaCl samples were reacted at fixed activities of H2O = 0.078, 0.350, 0.425, 0.448, 0.553, 0.560, 0.606, 0.678, 0.798, 0.841, and 0.935 to define the tie lines of known H2O activity in the halite-vapor and vapor-brine fields. Results indicate that fluids with all but the last of these H2O activities lie in the vapor-halite two-phase region and that a fluid with aH2O = 0.841 has a composition close to the three-phase (vapor + brine + halite) field. A second set of experiments was performed to determine the solubility of NaCl in parts of the system in equilibrium with halite. Data from these experiments suggest that the vapor corner of the three-phase field lies at H2O contents above XH2O = 0.58 and XNaCl = 0.06, and below XH2O = 0.75 and XNaCl = 0.06, which is a significantly more H2O-rich composition than indicated by existing thermodynamic models.